Evaluating pediatric antimicrobial dosing of β-lactam antibiotics for upper respiratory tract infections in emergency and primary care settings - Blower, Noah; Draper, Heather M; McAlpine, Tara; Dumkow, Lisa E (American journal of health-system pharmacy, 2025)
Pediatric prescribing is often weight and indication specific and has been associated with high rates of error. The aim of this study was to evaluate outpatient β-lactam suspension dosing practices for pediatric upper respiratory tract infections (URIs), to characterize the rate of error and to describe common error types. This retrospective cohort study was conducted at a community health system with 2 emergency departments and 20 outpatient family medicine practices. Pediatric patients treated from these settings with oral suspension formulations of amoxicillin, amoxicillin/clavulanate, cefdinir, or cephalexin for streptococcal pharyngitis or otitis media between June 1, 2020, and May 31, 2023, were eligible for inclusion. Doses were evaluated against indication-specific best-practice guidelines and assessed for guideline concordance. Of the 200 patients evaluated, 100 were treated for streptococcal pharyngitis and 100 were treated for otitis media. Of the prescribed β-lactam doses, 32% were discordant with best-practice guideline recommendations. Dosing errors were more common for pharyngitis than for otitis media (47% vs 17%; P < 0.001). Overdosing was the most frequently observed error in pharyngitis prescriptions (93.6% of errors) and most commonly occurred in patients weighing more than the 20-kg weight associated with the dosing maximum (80.9% of overdosing errors). All patients receiving an inappropriate dose for otitis media were underdosed. Outpatient pediatric dosing errors for URI indications are common among both emergency medicine and family medicine prescribers. Patients weighing over the weight corresponding to the dosing maximum are at highest risk for error. Antimicrobial stewardship interventions targeting the point of prescribing are urgently needed to provide safe dosing practices for pediatric patients.